Original paperProblems that occurred during and after transcatheter closure of muscular ventricular septal defects in two patients - Szkutnik, Małgorzata; Białkowski, Jacek; Dymitrow, Lyubomir; Kaneva, Anna; Lazarov, Stoyan; Tsonzarova, Margarita (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Aim: A case of 2 children (8 and 11-year-old), in whom muscular vetricular septal defect (mVSD) (in echo 5 and 6 mm of diameter respectively) was closed interventionally. Both had symptoms of significant left-right shunt. Methods and results: In the first patient 6 mm Amplatzer Muscular VSD Occluder (MVSDO) was implanted from the arterial side. The reason were technical problems to cross VSD with delivery system from the venous side. In the second child (with inlet defect) 8 mm MSDO was applied. During both procedures no complications were observed. In the latter case 3 days after the procedure important tricuspid valve incompetence was noted. The implant was removed, VSD closed and damaged tricuspid valve reconstructed surgically. Conclusion: During and after transcatheter closure of muscular ventricular septal defects unpredictable problems and complications can occur.